Dynamic Response Analysis of Sudden Enlargement and Sudden Contraction Pipe Conveying Fluid at Different End Conditions Using a Finite Element Method - Al-Baheli, Ali Mohammed Ridha Mahdi (Basrah Journal for Engineering Sciences, 2012)
Dynamic behavior of pipe conveying fluid at different cross section is investigated. Three kinds of supports are used, which are flexible, simply and rigid supports. The type effect of support on vibration characteristics and dynamic specification are studied. Also, the effect of some design parameters such as pipe material and Reynold numbers are investigated. The governing equations of motion for this system are derived using the finite element method which depends on beam theory. A finite element software (ANSYA-11) is presented to find first three eigenvalue (natural frequency) and eigenvector (mode shape) for pipe system in modal analysis. Velocity and pressure distribution are evaluated in a single phase fluid flow. A coupled field fluid-structure analysis was then performed by transferring fluid forces, solid displacements, and velocity across the fluid-structure interface. Finally the effective stresses (Von mises stress) in piping system are predicted in static analysis at various Reynold numbers, pipe material and pipe supports.